Christianity and politics - Anna Haapalainen; Minna Opas; Marika Räsänen (DONNER INST RESEARCH RELIGIOUS & CULTURAL HISTORY, 2022)
The editorial presents the conference "Religion and Politics" arranged by the Centre for the Study of Christian Cultures at the University of Turku in November 2018. Articles 3-7 of the current issue are based on papers presented at the conference.